Biomorphic SiC from peas and beans - Kiselov, V.S.; Yukhymchyk, V.A.; Poludin, V.I.; Tryus, M.P.; Belyaev, A.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Biomorphic porous SiC ceramics produced by impregnation with liquid or
vapor silicon of carbon matrices derived from peas (Pisum sativum L.) and beans
(Phaseolus) precursors were investigated. Optical and scanning electron microscopy was
used to study the structure of ceramics. It was shown that SiC ceramics made from
endosperm of peas and beans seeds has inherited the alveolate structure and possesses
many hierarchical pores with diameters varying between 20 to 100 µm. Raman
spectroscopy investigations showed that the 3C polytype is formed at a synthesis
temperature of about 1550 ⁰C, and that both 3C and 6H-SiC are formed at temperatures
of about 1800 ⁰C. It is shown possibilities of production of ceramic articles of various
forms from seeds.